Positive childhood experiences and subjective well-being among university students in Yunnan Province, China: The mediating role of psychological resilience - Yanni Huang; Fuhua Yang; Keli Yin (PLoS ONE, 2026)
This study examines the impact of Positive Childhood Experiences (PCEs) on the Subjective Well-Being (SWB) of university students in Yunnan Province, China, with psychological resilience as a mediating factor. Data were collected from 1,104 students across four universities using the Positive Childhood Experiences Scale, the Connor-Davidson Resilience Scale (CD-RISC), and measures of SWB. Descriptive statistics and mediation analysis were conducted using SPSS and the PROCESS macro. The results indicate that PCEs have a significant positive effect on SWB, and this relationship is partially mediated by psychological resilience. The indirect effect of PCEs on SWB through resilience was statistically significant. These findings highlight the importance of fostering resilience to enhance well-being in educational contexts. Given the regional focus on Yunnan Province, caution is warranted when generalizing the findings. Future research should examine broader and more diverse populations.